Avant le A d’Amazonie - Stéphen Rostain (Caravelle)
Archaeology in the Amazon basin has known a remarkable development for the last twenty years, after a late start in the middle of the 20th century, and a long period of seclusion because of the yoke of ecologic determinism. The most ancient human traces in the Amazon basin have been estimated to be dating back to over more or less 10 000 years. Later on, crucial events for the South American man would unfold little by little in the Amazon basin: the birth of pottery, the turning into cultivated varieties of many wild plants. More recently, the first European conquerors found complex and stratified societies on the river bank.